2001
DOI: 10.1074/jbc.m010427200
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Membrane Microtopology on Effective Two-dimensional Affinity

Abstract: Just as interactions of soluble proteins are affected by the solvent, membrane protein binding is influenced by the surface environment. This is particularly true for adhesion receptors because their function requires tightly apposed membranes. We sought to demonstrate, and further, to quantify the possible scale of this phenomenon by comparing the effective affinity and kinetic rates of an adhesion receptor (CD16b) placed in three distinct environments: red blood cells (RBCs), detached Chinese hamster ovary (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 23 publications
2
79
1
Order By: Relevance
“…These interactions can be impacted by the cell surface environment, as previously shown for membrane microtopology and stiffness (33,34). Another aspect of the membrane environment may be membrane rafts into which CD8 can partition (4).…”
Section: Disruption Of Membrane Rafts Differentially Reduces Affinitymentioning
confidence: 98%
See 1 more Smart Citation
“…These interactions can be impacted by the cell surface environment, as previously shown for membrane microtopology and stiffness (33,34). Another aspect of the membrane environment may be membrane rafts into which CD8 can partition (4).…”
Section: Disruption Of Membrane Rafts Differentially Reduces Affinitymentioning
confidence: 98%
“…More importantly, the two interacting cells have to be brought together because membranes separated by a distance greater than the molecular size would physically preclude binding. It has been demonstrated that the molecular length and orientation (32) as well as cell surface microtopology and stiffness can significantly affect 2D (but not 3D) affinity (33,34). Although the reverse-rate k r has the same unit (in s Ϫ1 ) for 2D and 3D interaction, only in the 2D (but not 3D) case can k r be regulated by force applied to the molecular bonds-they would be disrupted by the separation of the cells (31).…”
mentioning
confidence: 99%
“…For example, although having no impact to 3D affinity, reducing flexibility by shortening the length and randomizing the orientation of some receptor-ligand molecules has been found to decrease 2D affinity by reducing 2D on-rate but not 2D off-rate (17). Disrupting the smoothness and continuity of the confinement zone by surface roughness has been shown to reduce the effective 2D affinity (18). Conformational changes in the binding site have been shown to result in different changes in the 2D and 3D on-rates and off-rates (19).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Also, a recent study has demonstrated that membrane roughness can modulate the effective affinity of membrane proteins (33). Taken together with the unexpectedly high values for antibodies and SEC3 variants on surface A, it appeared possible that chemical changes of the ligand-presenting surface could enhance the 2D-affinity of immobilized ligands.…”
Section: Direct Fitting Of T Cell Responses Againstmentioning
confidence: 99%